Pengaruh Suara Adzan Terhadap Pertumbuhan, Produksi, Dan Kejadian Penyakit Pada Tiga Jenis Tanaman Brassicaceae - Agung Jabar Nur; Ahmad Rafiqi Tantawi; Syahbudin Hasibuan (Universitas Medan Area, 2021)
Plants can listen to sounds and respond to these sounds by changing metabolic activity. A good sound will have a positive effect on plant metabolism and vice versa. The adhan to prayer is a call to pray and contains good sentences. This study aims to determine the effect of the sound of the adhan on the growth, production, and disease incidence of the Brassicaceae family. This was conducted by performing split plot design which consisted of 2 factors namely plants spesies and the sound of the adhan. The plant species consisted of 3 treatment levels, namely: A1= Mustard greens, A2= Kailan, A3= Pakcoy. Meanwhile, frequency of the adhan consists of 7 levels, namely: B0= without adhan, B1= 2 times a day, B2= 3 times a day, B3= 4 times a day, B4= 5 times a day, and B5= 6 times a day. The results showed that there was a tendency for differences in plant height, leaf area, plant total fresh weight and net weight given the sound of the adhan compared to without sound, but statistically it was not significantly different. The more often the plant is played the sound of the adhan can increase the production of the brassicaceae family.